What's the point of sport?. Issue 2 (3rd April 2019) - Murray, Thomas H.
ABSTRACT: The fundamental reality of elite sport is the relentless competitive dynamic that drives it. In most cases, the top athletes, in any event, are evenly matched except for small but decisive differences in talent and dedication. Doping is an ever-present threat to distort the results that talent and dedication would otherwise dictate. The fundamental goal and justification for anti-doping are to allow non-doping athletes to compete against other clean athletes with reasonable confidence that the contest will be decided by whatever mix of talents, dedication and tactics ought to be decisive according to that sport's understanding of its meaning and values. There are many answers to the question what is the point of sport. Three stand out as important and influential in the debate over the ethics of doping: that sport is a quest for extreme feats; that sport should focus on rewarding virtuous and admirable attributes such as hard work, persistence and courage; or that sport should also embrace natural talents as an inescapable component of excellence in sport. The most plausible account of the point of sport is as a vehicle to encourage and celebrate the virtuous perfection of natural talents. It accords well with settled judgments, broadly accepted practices, and rational principles in the manner described by Rawls in his discussions of reflective equilibrium. This article considers representative moral and conceptual arguments against this standard before outlining the arguments in its favour. Sport urgently needs reforms in governance along with a clear articulation of its moral foundation.